Simulation and Implementation of Bluetooth Wireless Home Automation System - Yusuf, Samson Dauda; Egbebi, Lukman Femi; Loko, Abdulmumini Zubairu (Review of Information Engineering and Applications, 2022)
The stress and difficult experience undergone by the old aged and disabled persons in manually operating their home appliances is a major concern in this present day of rising burglary and other insecurities in Nigeria. In this study, simulation an implementation of a Bluetooth wireless home automation system was carried out using a microcontroller. The design comprised an Arduino ATmega328 microcontroller board, Bluetooth module (HC-06), and Massachusetts Institute of Technology (MIT) App Inventor 2 for android. The Arduino was programmed with C++ programming language by using Integrated Development Environment (IDE). Relays and Triacs were used for the switching mechanism. The software design was achieved using Proteus 8.0, while the hardware prototype was constructed on a Vero board and a performance analysis of the designed circuit was carried out. Result shows that, once the system is connected, the user can controls his electrical appliances by switching them ON and OFF using either the android app Bluetooth module, the IR remote control or the push button on the device. The system application is easy to use, user friendly and convenient to operate via any of the provided alternatives. The Bluetooth wireless home automation system makes life easier for the home owners especially the old aged and disables and prevent energy wastage. With addition of biometrics, it can also prevent unauthorized access to homes and thereby reduce the case of burglary and other insecurity treats at homes.